Hotel Resort Tongging with Approachment of Neo Vernacular Architecture (International Journal of Architecture and Urbanism, 2019)
This journal is about the design process of Resort Hotels located in Tongging by adopting a Neo Vernacular design approach into the building. The problem in this design process is how to apply the Neo-Vernacular architecture approach to this Resort Hotel building. How to create comfortable outdoor and indoor space for visitors to the tourist area?. How to choose the right material according to the current temperature and conditions, so that it can support the character of the building. The purpose of this design is to apply the Neo-Vernacular Architecture approach to the Tongging Resort Hotel building by looking at the locality context, and designing the out and inside spaces that are comfortable for visitors by uniting indirectly between both areas. Choose the right material according to the temperature and existing conditions, to support the building's character. The methodology carried out in this design was location survey (physical data collection), comparative study, literature study, data processing, conceptualization, schematic and arrived at the final design. The discovery in this design is to design a building that is in an area that has strong locality must do research and analysis to get the concept that is suitable and can be received by the surrounding community and visitors. The author also found that the selection of building materials should source from the site location. For general people, this design is useful as a reference to help similar design buildings.